2017
DOI: 10.3390/s18010017
|View full text |Cite
|
Sign up to set email alerts
|

Design and Development of a Wearable Device for Heat Stroke Detection

Abstract: Heat stroke can be potentially damaging for people while exercising in hot environments. To prevent this dangerous situation, we designed a wearable heat-stroke-detection device (WHDD) with early notification ability. First, we used several physical sensors, such as galvanic skin response (GSR), heart beat, and body temperature, to acquire medical data from exercising people. In addition, we designed risk evaluation functional components that were based on fuzzy theory to detect the features of heat stroke for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 19 publications
0
21
0
1
Order By: Relevance
“…The complete WHDD is shown in Figure 2. Detailed descriptions of the different components of the device can be found in our previous work [21].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The complete WHDD is shown in Figure 2. Detailed descriptions of the different components of the device can be found in our previous work [21].…”
Section: Methodsmentioning
confidence: 99%
“…The system suggests to the runner to ensure that appropriate measures are immediately taken in a dangerous situation to avoid heat stroke. The details of these procedures can be found in our previous work [21].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors suggested the possible application of proposed approach for the extraction and comparison of sleep movements' patterns in the field of medicine. Based on a previous work of a Wearable Heat stroke Detection Device (WHDD) [8] that was used for heat stroke prediction capability for any activity or exercise. Lin et al [9] investigated the detailed information analysis and performed static and dynamic experiments for verifying the availability and effectiveness of WHDD experimental subjects.…”
Section: Summary Of Special Issue Papersmentioning
confidence: 99%